Dual Effect by Chemical Electron Transfer Enhanced siRNA Lipid Nanoparticles: Reactive Oxygen Species-Triggered Tumor Cell Killing Aggravated by Nrf2 Gene Silencing - Fengrong Zhang; Tobias Burghardt; Miriam Höhn; Ernst Wagner (MDPI AG, 2024)
Insufficient endosomal escape presents a major hurdle for successful nucleic acid therapy. Here, for the first time, a chemical electron transfer (CET) system was integrated into small interfering RNA (siRNA) lipid nanoparticles (LNPs). The CET acceptor can be chemically excited using the generated energy between the donor and hydrogen peroxide, which triggers the generation of reactive oxygen species (ROS), promoting endosomal lipid membrane destabilization. Tetra-oleoyl tri-lysino succinoyl tetraethylene pentamine was included as an ionizable lipopeptide with a U-shaped topology for effective siRNA encapsulation and pH-induced endosomal escape. LNPs loaded with siRNA and CET components demonstrated a more efficient endosomal escape, as evidenced by a galectin-8-mRuby reporter; ROS significantly augmented galectin-8 recruitment by at least threefold compared with the control groups, with a p value of 0.03. Moreover, CET-enhanced LNPs achieved a 24% improvement in apoptosis level by knocking down the tumor-protective gene nuclear factor erythroid 2-related factor 2, boosting the CET-mediated ROS cell killing.